2002
DOI: 10.1021/om020251b
|View full text |Cite
|
Sign up to set email alerts
|

α-Iminoenamido Ligands:  A Novel Structure for Transition-Metal Activation

Abstract: This communication shows that it is possible to activate nickel complexes containing the R-iminoenamide ligand using B(C 6 F 5 ) 3 or Al(C 6 F 5 ) 3 to generate catalysts that polymerize ethylene. The polymerization of ethylene using these novel compounds is discussed. The novel activation method is confirmed by the X-ray crystallography studies of the methallyl analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 23 publications
3
57
0
Order By: Relevance
“…This is in good agreement with the observed high activity reported for late-transition-metal polymerization catalysts that bear electron-deficient ligands. [25,26] Furthermore, as a reviewer pointed out, for the catalyst that bears 2-[2,6-(MeO) 2 C 6 H 3 ]-C 6 H 4 -aryl groups, the bulk is mostly located in the axial faces. [12] By contrast, it is possible to imagine that catalysts 3Pd to 5Pd are encumbered in the complex plane, with the result that monomer coordination is slowed, but with no rate decrease for β-H elimination.…”
Section: Resultsmentioning
confidence: 99%
“…This is in good agreement with the observed high activity reported for late-transition-metal polymerization catalysts that bear electron-deficient ligands. [25,26] Furthermore, as a reviewer pointed out, for the catalyst that bears 2-[2,6-(MeO) 2 C 6 H 3 ]-C 6 H 4 -aryl groups, the bulk is mostly located in the axial faces. [12] By contrast, it is possible to imagine that catalysts 3Pd to 5Pd are encumbered in the complex plane, with the result that monomer coordination is slowed, but with no rate decrease for β-H elimination.…”
Section: Resultsmentioning
confidence: 99%
“…4.9) [127]. A canonical structure (Scheme 4.7 right) has coordination of the diimine ligand to the Ni center, similar to the structure of the active species of the Brookhart's diimine Ni catalyst [130]. The complex catalyzes ethylene polymerization to produced polyethylene with a branched structure (33-106 branches per 1,000 carbons).…”
Section: Catalyst Having Tropone-imide Type Ligandsmentioning
confidence: 98%
“…The intervals between the six-membered rings are determined by the spacer length between the vinyl and cyclohexyl groups of the monomer. Depending on the density of the cyclohexane group, the melting point of the polymer can be varied from 130 . Due to the steric repulsion between the bulky aryl substituents, the two N-aryl planes are twisted from each other.…”
Section: A/mmaomentioning
confidence: 99%
“…1 H NMR (500 MHz, C 6 D 6 , 25°C. Two sets of peaks (9:1 ratio) were observed): major isomer, d , some signals of the minor isomer were not seen due to the overlap with those of the major isomer; 13 …”
Section: -(26-diisopropylphenylimino)-but-1-en-2-olato (G 1 -Benzylmentioning
confidence: 99%
“…Examination of ligand/reactivity relationships for cationic Ni(diimine) initiators [2,8] led to the design and synthesis of {(H 3 C)C[@NAr]C[O-B(C 6 F 5 ) 3 ][@NAr]-j 2 N,N 0 }-Ni(g 3 -CH 2 C 6 H 5 ), with which high molecular weight polyethylene (PE) can be produced for bulky aromatic (Ar) substituents [9]. Several other ligand types have been reported that are amenable to the concept of Lewis acid attachment on a ligand site to redistribute electron density, including 3-(1-arylimino-ethyl)-acetylacetonato [10], 2-diphenylphosphinylbenzamido [11], N-(2-benzoylphenyl)-benzamido [12], a-iminoenamido [13], 2-(alkyldeneamino)-benzoato [14] and iminoamido pyridine [15], However, none of these systems have been able to produce high molecular weight PE in the absence of bulky Ar substituents.…”
Section: Introductionmentioning
confidence: 99%